Analysis of the Effect of Job Motivation, Career Development on Interest in Working Transfer with Job Satisfaction Mediation (Case Study PT KAI DAOP 5) - Rana Khairunnisa; Yudi Nur Supriadi; Acim Heri Iswanto (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study aims to determine the effect of work motivation system, career development on turnover intention by mediating job satisfaction at PT KAI DAOP 5. Turnover intention is one of the inhibiting factors in achieving company goals. The type of this research is quantitative, using simple random sampling questionnaire data collection technique, the research is 105 respondents who are employees of PT KAI DAOP 5 with an age range of 40-55 years. By using data analysis techniques using SmartPLS 3.0 to get the results of the validity, reliability, and hypothesis testing. The results of this study indicate that work motivation has significant effect on job satisfaction, work motivation has no significant effect on turnover intention, career development has a significant effect on job satisfaction, career development has no significant effect on turnover intention, job satisfaction has a significant effect on turnover intention, work motivation has a significant effect on turnover intention through job satisfaction, career development has a significant effect on turnover intention through job satisfaction. Keywords : work motivation, career development, job satisfaction and turnover Intention